Understanding the role of physician attire on patient perceptions: a systematic review of the literature— targeting attire to improve likelihood of rapport (TAILOR) investigators. Issue 1 (19th January 2015) - Petrilli, Christopher Michael; Mack, Megan; Petrilli, Jennifer Janowitz; Hickner, Andy; Saint, Sanjay; Chopra, Vineet
Abstract : Objectives: Despite a growing body of literature, uncertainty regarding the influence of physician dress on patients' perceptions exists. Therefore, we performed a systematic review to examine the influence of physician attire on patient perceptions including trust, satisfaction and confidence. Setting, participants, interventions and outcomes: We searched MEDLINE, Embase, Biosis Previews and Conference Papers Index. Studies that: (1) involved participants ≥18 years of age; (2) evaluated physician attire; and (3) reported patient perceptions related to attire were included. Two authors determined study eligibility. Studies were categorised by country of origin, clinical discipline (eg, internal medicine, surgery), context (inpatient vs outpatient) and occurrence of a clinical encounter when soliciting opinions regarding attire. Studies were assessed using the Downs and Black Scale risk of bias scale. Owing to clinical and methodological heterogeneity, meta-analyses were not attempted. Results: Of 1040 citations, 30 studies involving 11 533 patients met eligibility criteria. Included studies featured patients from 14 countries. General medicine, procedural (eg, general surgery and obstetrics), clinic, emergency departments and hospital settings were represented. Preferences or positive influence of physician attire on patient perceptions were reported in 21 of the 30 studies (70%). Formal attire and white coats with other attire not specified was preferred in 18 of 30 studies (60%). Preference for formal attire and white coats was more prevalent among older patients and studies conducted in Europe and Asia. Four of seven studies involving procedural specialties reported either no preference for attire or a preference for scrubs; four of five studies in intensive care and emergency settings also found no attire preference. Only 3 of 12 studies that surveyed patients after a clinical encounter concluded that attire influenced patient perceptions. Conclusions: Although patients often prefer formal physician attire, perceptions of attire are influenced by age, locale, setting and context of care. Policy-based interventions that target such factors appear necessary.